1998
DOI: 10.1044/jslhr.4103.527
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss, Control, and Demographic Factors Influencing Hearing Aid Use Among Older Adults

Abstract: Preference for non-use of hearing aids among older adults who are candidates for amplification remains to be explained. Clinical studies have examined the contribution of consumer attitudes, behaviors, and life circumstances to this phenomenon. The present study extends the interests of earlier investigators in that it examines psychological control tendencies in combination with hearing loss and demographic variables among older adults who elected to accept (adherents) or ignore (nonadherents) advice from hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
2
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 27 publications
7
130
2
7
Order By: Relevance
“…Non-ideal performance with hearing aids in these cases reflects in auditory processing disorders. Garstecki and Erler (1998) noticed that patients with sound intolerance would have deficit in their skills to benefit from the use of hearing aids. This finding is in accordance with the pathophysiological characteristics of hearing loss, since as previously demonstrated, if patients have sensorineural hearing loss, intolerance to loud sounds and tinnitus they are less benefited by acoustic amplification, and so it is expected that they would be less satisfied with the results obtained with hearing aids.…”
Section: Discussionmentioning
confidence: 99%
“…Non-ideal performance with hearing aids in these cases reflects in auditory processing disorders. Garstecki and Erler (1998) noticed that patients with sound intolerance would have deficit in their skills to benefit from the use of hearing aids. This finding is in accordance with the pathophysiological characteristics of hearing loss, since as previously demonstrated, if patients have sensorineural hearing loss, intolerance to loud sounds and tinnitus they are less benefited by acoustic amplification, and so it is expected that they would be less satisfied with the results obtained with hearing aids.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps that is what draws them to getting amplification. In fact, Garstecki and Erler (1998) suggested that individuals with low expectations often rejected a hearing aid recommendation; however, unrealistically high expectations also seemed to cause problems with acceptance of amplification. Whether expectation changes over time is uncertain.…”
Section: Expectationmentioning
confidence: 99%
“…Previous studies have also identified greater hearing impairment as a predictor of help seeking and hearing aid ownership (e.g., Garstecki & Erler, 1998;Helvik, Wennberg, Jacobsen, & Hallberg, 2008;Swan & Gatehouse, 1990;van den Brink, Wit, Kempen, & van Heuvelen, 1996). In some instances, clinicians might contribute to this association by recommending hearing aids to people with a greater hearing impairment.…”
Section: Hearing Impairmentmentioning
confidence: 99%